2020
DOI: 10.3390/brainsci10100697
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells in the Auditory Periphery of Rodents

Abstract: Mast cells (MCs) are densely granulated cells of myeloid origin and are a part of immune and neuroimmune systems. MCs have been detected in the endolymphatic sac of the inner ear and are suggested to regulate allergic hydrops. However, their existence in the cochlea has never been documented. In this work, we show that MCs are present in the cochleae of C57BL/6 mice and Wistar rats, where they localize in the modiolus, spiral ligament, and stria vascularis. The identity of MCs was confirmed in cochlear cryosec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The spiral prominence showed rare cells expressing CD117 (KIT). Recently, mast cells were localized in the mouse and rat modiolus, spiral ligament, and stria vascularis using antibodies against c-Kit/CD117 ( 78 ). Their role in cochlear development, homeostasis, and pathology was discussed.…”
Section: Discussionmentioning
confidence: 99%
“…The spiral prominence showed rare cells expressing CD117 (KIT). Recently, mast cells were localized in the mouse and rat modiolus, spiral ligament, and stria vascularis using antibodies against c-Kit/CD117 ( 78 ). Their role in cochlear development, homeostasis, and pathology was discussed.…”
Section: Discussionmentioning
confidence: 99%
“…A few research teams have identified the expression of histamine receptors in the inner ear of mammals [38][39][40][41]. Additionally, in 2020, our group found mast cells in the inner ear of both rats and mice [42]. Mast cells are the major source of histamine in the body, along with basophils, gastric parietal cells, and the central nervous system [43].…”
Section: Introductionmentioning
confidence: 89%
“…Postnatal mouse brain and adult mouse spleen tissues were harvested and used as positive and negative controls, respectively. The Western blot protocol was previously described [ 51 ]. Briefly, the tissue lysates were prepared by placing and vortexing the explants in 80 µL RIPA buffer (Cell Signaling Technology, Danvers, MA, USA) and then centrifuging them at 14,000 RPM at +4 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%